A continous Tendon-Driven Delta Robot - The Dr. Otto Octavius Project (2024)
This document presents the design, implementation, and testing of a Tendon-Driven Continuum Robot (TDCR) named "Dr. Otto Octavius." The project aims to explore the capabilities and applications of a soft robotic system driven by tendons, similar to the muscular structure of an octopus. The robot consists of multiple segments and sections connected by joints, actuated by tendons controlled via a custom-designed electronic and communication system.The report details the mechanical design, including the structure and assembly of the robot, and the development of the control electronics, emphasizing the integration of an Inertial Measurement Unit (IMU) system for precise motion tracking. Calibration procedures for both initial offsets and movement verification are described to ensure accurate control and operation of the robot. Furthermore, the document includes an analysis of the robot’s performance in executing various movements and provides troubleshooting guidelines and maintenance recommendations. The project demonstrates the potential of TDCRs in accessing difficult-to-reach areas, assisting in manufacturing processes, and supporting individuals with disabilities, highlighting the versatility and adaptability of soft robotic systems.